Epitope mapping of novel monoclonal antibodies to human angiotensin I‐converting enzyme. (11th May 2021) - Popova, Isolda A.; Lubbe, Lizelle; Petukhov, Pavel A.; Kalantarov, Gavriil F.; Trakht, Ilya N.; Chernykh, Elena R.; Leplina, Olga Y.; Lyubimov, Alex V.; Garcia, Joe G.N.; Dudek, Steven M.; Sturrock, Edward D.; Danilov, Sergei M.
Abstract: Angiotensin I‐converting enzyme (ACE, CD143) plays a crucial role in blood pressure regulation, vascular remodeling, and immunity. A wide spectrum of mAbs to different epitopes on the N and C domains of human ACE have been generated and used to study different aspects of ACE biology, including establishing a novel approach–conformational fingerprinting. Here we characterized a novel set of 14 mAbs, developed against human seminal fluid ACE. The epitopes for these novel mAbs were defined using recombinant ACE constructs with truncated N and C domains, species cross‐reactivity, ACE mutagenesis, and competition with the previously mapped anti‐ACE mAbs. Nine mAbs recognized regions on the N domain, and 5 mAbs–on the C domain of ACE. The epitopes for most of these novel mAbs partially overlap with epitopes mapped onto ACE by the previously generated mAbs, whereas mAb 8H1 recognized yet unmapped region on the C domain where three ACE mutations associated with Alzheimer's disease are localized and is a marker for ACE mutation T877M. mAb 2H4 could be considered as a specific marker for ACE in dendritic cells. This novel set of mAbs can identify even subtle changes in human ACE conformation caused by tissue‐specific glycosylation of ACE or mutations, and can detect human somatic and testicular ACE in biological fluids and tissues. Furthermore, the high reactivity of these novel mAbs provides an opportunity to study changes in the pattern of ACE expression or glycosylation in different tissues, cells, and diseases, such as sarcoidosis and Alzheimer's disease.